2012
DOI: 10.3168/jds.2011-4696
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus kefiranofaciens M1 isolated from milk kefir grains ameliorates experimental colitis in vitro and in vivo

Abstract: Lactobacillus kefiranofaciens M1, isolated from and identified in Taiwanese milk kefir grain, has demonstrated immune-modulating activity. In the present study, we further investigated the effects of Lb. kefiranofaciens M1 on intestinal epithelial cells in vitro and on dextran sodium sulfate (DSS)-induced colitis in vivo. The possible mechanisms regarding the cytokine products and intestinal epithelial barrier restoration as well as the putative receptor for the protective effects of Lb. kefiranofaciens M1 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 57 publications
1
67
0
1
Order By: Relevance
“…Namely, the results of this present study showed a very similar trend with those of various previous studies (Simova et al, 2002: Ntsame Affane et al, 2011Chen et al, 2012). Among of many beneficial factors of flaxseed, the flaxseed lignan SECO (secoisolariciresinol) and its diglucoside SDG (SecoisolariciresinolDiglucoside) were recognized as having various benefits for health.…”
Section: The Statistical Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Namely, the results of this present study showed a very similar trend with those of various previous studies (Simova et al, 2002: Ntsame Affane et al, 2011Chen et al, 2012). Among of many beneficial factors of flaxseed, the flaxseed lignan SECO (secoisolariciresinol) and its diglucoside SDG (SecoisolariciresinolDiglucoside) were recognized as having various benefits for health.…”
Section: The Statistical Analysissupporting
confidence: 80%
“…When compared to previous researches, the range of pH normally reported for Kefir samples was 3.5~4.5 and the range of TA varied between 0.50 and 1.50 g 100 mL -1 (Simova et al, 2002: Chen et al, 2012, and the appropriate range of pH for a commercially available yogurt was between 3.27 and 4.53, and the value of TA was in the range of 0.7% and 1.20% (Adolfsson et al, 2004).…”
Section: The Statistical Analysismentioning
confidence: 99%
“…L. jensenii can suppress IL-8 induced by TLR ligands [63]. A nonvaginal Lactobacillus species induced production of proinflammatory protein MIP-3a [64]. Vaginal pathogens, associated with BV such as Atopobium vaginae and Prevotella bivia induced simultaneous NF-jB activation and upregulation of proinflammatory proteins in contrast to vaginal strains L. crispatus, L. acidophilus and L. jensenii [28,62].…”
Section: Resultsmentioning
confidence: 97%
“…Probiotics produce proteases that directly degrade C. difficile toxins and increase the immune response to the toxins (McFarland, 2009). Saccharomyces boulardii reduced toxin-induced intestinal secretion and permeability, produced toxin-degrading proteases, and inhibited binding of toxins to the brush border membrane (Chen et al, 2012).…”
Section: Cholesterol-lowering Effectsmentioning
confidence: 99%